US Rural Surgeon Responses to the COVID-19 Pandemic: Leadership in a Time of Crisis. Issue 6 (June 2020) - Sarap, Michael; Conyers, Julie; Cunningham, Crystal; Deutchman, Adam; Levine, Glenn; Long, Sue; Molt, Patrick; Rossi, Matt; Welsh, David; Hughes, Dorothy
Nine surgeons from rural and remote communities in the United States share early experiences preparing for the COVID-19 pandemic. Relating experiences remarkably different from health care providers in urban areas in America most affected by the first stages of the outbreak, they tell the challenges of organizing resources in facilities already struggling with poverty-stricken communities far from established health care resources and supplies. From Alaska to Appalachia and the Navajo Nation to the rural midwest, they show the leadership and professionalism that exemplify rural surgery.